Los tres universos de la libertad en la evolución del Estado - Bonavides, Paulo (2013)
"Bachelor of Legal and Social Sciences from the National University of Law of the University of Brazil (1948). Doctor of Law from the Federal University of Ceará. Doctor honoris causa from the Federal University of Rio de Janeiro and the University of Buenos Aires, among other academies. Professor Emeritus of the Faculty of Law of the National University of Ceará."